Sustainable Supply Chain Management Learning from the German Automotive Industry - Rausch-Phan, Minh Trang; Siegfried, Patrick (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the current causes and effects of implementing sustainable supply chain management (SSCM) as well as green supply chain management (GSCM) strategies in the automotive industry. The reader is provided a detailed scientific review on SSCM and GSCM and presented the advantages of sustainable development concepts as well as factors causing the implementation of SSCM such as buyers' behavior, governmental regulations, and competitiveness. The book then analyses the current situation of SSCM development, particularly in the automotive industry. It shows challenges, barriers, successes, and benefits that automotive companies obtain from implementing GSCM. Through case studies on leading German car manufacturers VW, BMW, and Daimler, the necessary activities of these companies to implement green development in the entire supply chain, including green supplier selection, green materials, green transportation, and reverse logistics, are defined. Moreover, a benchmark with companies from Asian markets such as Toyota from Japan and Geely from China is performed.
1. Introduction of Sustainable Supply Chain Management: Learning from the German Automotive Industry -- 2. Traditional Supply Chain Management -- 3. Sustainable Supply Chain Management -- 4. Green Supply Chain Management -- 5. Scenarios and Concepts for the Future Development -- 6. Conclusion of Sustainable Supply Chain Management: Learning from the German Automotive Industry.
Keywords: Automobile industry and trade; Business logistics; Sustainability; Industrial management-Environmental aspects; Automotive Industry; Supply Chain Management; Sustainability; Corporate Environmental Management